Congenital Muscular Torticollis And Dissociation Clinicalultrasound In The Newborn: Case Report - Quispe-Condori, Custodio Olsen (2016)
The congenital muscular torticollis is an entity clinical known from the antiquity, is characterized by present a deviation of thehead with tilt and rotation towards the side affection, the chin rotates in the opposite direction; that produces throughout herlife a defect functional important of the neck and a defect aesthetic considerable.The risk factors are: obstetric, maternal and fetal. The clinical manifestations are evident at birth, whose diagnosis is confirmedwith ultrasound requested in the course of the first two days of life. Sometimes ultrasound does not contribute to confirmthe clinical diagnosis evident. This fact is known as dissociation clinical ultrasound. Management of congenital musculartorticollis should start as soon as the diagnosis is made and keep in mind that the ultrasound is an auxiliary examination. Itis important to assess the expertise of the evaluator in decision-making process. A case is presented of the newborn twin1, birth vaginally, with congenital muscular torticollis right and dissociation clinical ultrasound, which is evidenced with theviews and reports ultrasound; whose prognosis is good when it starts soon the management physiotherapist. The presentwork realized in the Institute National Materno Perinatal, has by objective contribute to the knowledge medical e exchangeexperiences in the diagnosis early of the congenital muscular torticollis and it reference timely to a center specialized for itsmanagement corresponding.